MicroRNA signatures characterizing caste-independent ovarian activity in queen and worker honeybees (Apis mellifera L.) - Macedo, L. M. F.; Nunes, F. M. F.; Freitas, F. C. P.; Pires, C. V.; Tanaka, E. D.; Martins, J. R.; Piulachs, M. -D.; Cristino, A. S.; Pinheiro, D. G. [UNESP]; Simoes, Z. L. P. (Wiley-Blackwell, 2016)
Queen and worker honeybees differ profoundly in reproductive capacity. The queen of this complex society, with 200 highly active ovarioles in each ovary, is the fertile caste, whereas the workers have approximately 20 ovarioles as a result of receiving a different diet during larval development. In a regular queen-right colony, the workers have inactive ovaries and do not reproduce. However, if the queen is sensed to be absent, some of the workers activate their ovaries, producing viable haploid eggs that develop into males. Here, a deep-sequenced ovary transcriptome library of reproductive workers was used as supporting data to assess the dynamic expression of the regulatory molecules and microRNAs (miRNAs) of reproductive and nonreproductive honeybee females. In this library, most of the differentially expressed miRNAs are related to ovary physiology or oogenesis. When we quantified the dynamic expression of 19 miRNAs in the active and inactive worker ovaries and compared their expression in the ovaries of virgin and mated queens, we noted that some miRNAs (miR-1, miR-31a, miR-13b, miR-125, let-7 RNA, miR100, miR-276, miR-12, miR-263a, miR-306, miR-317, miR-92a and miR-9a) could be used to identify reproductive and nonreproductive statuses independent of caste. Furthermore, integrative gene networks suggested that some candidate miRNAs function in the process of ovary activation in worker bees.
Keywords: microRNA; transcriptome; ovary; plasticity; development; honeybee